Binder for improving dispersion uniformity of self-heating body and preparation method thereof

By modifying starch and sodium carboxymethylcellulose to form a crosslinked structure, the chemical bonding and π-π stacking effect are used to form specific groups with active metals and carbon powder, the problem of uneven dispersion of active metals and carbon powder is solved, and the performance of the self-heating body is improved.

CN119859484AInactive Publication Date: 2025-04-22ZHEJIANG ZHENSHI MINGYAN HEALTH IND CO LTD

Patent Information

Application Number
CN202510054492.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-22
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing binders cannot effectively disperse and tightly adhere to the active metals and carbon powders, resulting in the impact of the performance of the self-heating body.

Method used

Starch and sodium carboxymethylcellulose are used as the main raw materials, and a binder with a crosslinking structure is formed through modification and crosslinking reaction. Pyridine, hydroxyl and carboxy groups are used to form coordination bonds with the active metal, and phenyl groups form a π-π stacking effect with the carbon powder, achieving a tight bond between the active metal and the carbon powder.

Benefits of technology

The uniform dispersion and tight bonding of active metals and carbon powder are achieved, and the bonding performance, thermal expansion resistance and anti-aging properties of the self-heating body are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005240979150000031
    Figure BDA0005240979150000031
  • Figure BDA0005240979150000111
    Figure BDA0005240979150000111
  • Figure FDA0005240979140000011
    Figure FDA0005240979140000011
Patent Text Reader

Abstract

The invention relates to the technical field of binders, in particular to a binder capable of improving dispersion uniformity of a self-heating element and a preparation method of the binder. Environment-friendly biodegradable natural extract starch and sodium carboxymethyl cellulose are used as initial raw materials, and the starch and the sodium carboxymethyl cellulose are respectively and specifically modified to obtain the binder capable of improving the dispersion uniformity of the self-heating element. And carrying out Schiff base reaction on the modified starch and sodium carboxymethyl cellulose, and cross-linking to form the binder. The binder disclosed by the invention is suitable for a self-heating body, active metal and carbon powder can be uniformly dispersed and tightly bonded, and meanwhile, the binder has high bonding performance, thermal expansion resistance and aging resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesives, and in particular to an adhesive capable of improving the uniformity of dispersion of a self-heating body and a preparation method thereof. Background Art

[0002] Binder, also known as adhesive, is a non-metallic medium material widely used in the fields of construction, industry, home, etc. It can connect or stick the same or different materials together, and is the guarantee of the bonding strength between the abrasive and the substrate. With the development of the chemical industry, various new types of binders have entered the field of coated abrasives, significantly improving the performance of coated abrasives and promoting the progress of the coated abrasives industry.

[0003] There are many types of adhesives, which can be divided into natural adhesives and artificial adhesives according to the source of materials. Natural adhesives such as starch, dextrin, animal glue, shellac, hide glue, rosin, etc. are mainly taken from materials in nature, while artificial adhesives are artificially made, such as inorganic adhesives such as pellet adhesives and water glass, and organic adhesives such as synthetic resins and synthetic rubber. In addition, according to the use characteristics, adhesives can also be divided into water-soluble adhesives, hot-melt adhesives, solvent-based adhesives, emulsion adhesives, solvent-free liquid adhesives, etc. Adhesives have many advantages, such as wide application, easy use, high economic benefits, etc. They can connect similar or different materials, such as steel and aluminum, metal and glass, etc., simplify mechanical processing technology, shorten production cycle, improve production quality, reduce costs, etc. With the increasing global awareness of environmental protection, the environmental performance of binders has become an important direction for their development. For example, CN114656904B discloses "a binder and a battery comprising the binder". A new aqueous binder with self-crosslinking, high adhesion and good flexibility is obtained by copolymerizing multiple functional monomers. The binder is suitable for positive electrodes, is green and environmentally friendly, and has the characteristics of good cycle stability.

[0004] For example, CN110760282B discloses "an environmentally friendly water-based adhesive" which uses modified latex and modified APAO emulsion as the main raw materials, and adds powder particle skeleton material and thickener as auxiliary fillers. The adhesive has good viscosity, is pollution-free, has no VOC emissions, leaves no residue after use, is easy to clean, has no adverse effects on the environment, and is environmentally friendly and efficient.

[0005] For example, CN104629647B discloses "an environmentally friendly starch adhesive" which is made of polyvinyl alcohol, hydrochloric acid, starch, polyacrylamide, surfactants, preservatives and other raw materials through gelatinization, acidification, grafting and other chemical reactions. It has good bonding properties and water resistance.

[0006] The preparation of self-heating bodies often requires the addition of an appropriate amount of binder to make the active metals, carbon powder, etc. evenly dispersed and bonded together. However, the quality difference between the active metals and carbon powder is too large. During the mixing process, due to the influence of the quality difference, the two are prone to uneven mixing, and conventional binders are not suitable for this system.

[0007] Therefore, it is urgent to develop an adhesive that is suitable for self-heating elements, can evenly disperse active metals and carbon powder, make the two tightly bonded, and has high bonding properties. Summary of the invention

[0008] The main purpose of the present invention is to provide a binder for improving the uniformity of dispersion of self-heating bodies and a preparation method thereof. The binder is suitable for use in self-heating bodies, can disperse active metals and carbon powder evenly, and tightly bond the two together, while having high bonding properties, resistance to thermal expansion, and anti-aging properties.

[0009] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0010] The present invention provides a method for preparing a binder for improving the dispersion uniformity of a self-heating body, comprising the following steps:

[0011] S1. Disperse starch in deionized water, raise the temperature to 30-40° C., adjust the pH of the system to 8-9, then add an aqueous solution of 2,3-pyridinedicarboxylic anhydride, stir at a constant temperature for 2-4 hours, and control the pH of the system to be unchanged. After the reaction is completed, adjust the pH to neutral, rinse with anhydrous ethanol, and dry to obtain pyridine-modified starch;

[0012] S2, cooling thionyl chloride to -5 to 0°C, then adding the pyridine-modified starch in step S1, stirring at a constant temperature for 1 to 3 hours, filtering after the reaction, washing with ethanol, and drying to obtain acyl chloride-modified starch;

[0013] S3, mixing the acyl chloride modified starch in step S2 with N,N-dimethylformamide, adding 1,4-butanediamine and an acid binding agent, heating to 50-60° C. and stirring at a constant temperature for 12-18 hours, washing with deionized water after the reaction, concentrating and drying under reduced pressure to obtain a composite modified starch;

[0014] S4, mixing sodium carboxymethyl cellulose with deionized water, heating to 30-40°C and stirring at constant temperature for 12-16 hours, then adding NaIO4 solution thereto, adjusting the pH to 2-3, stirring at constant temperature for 4-6 hours under light-proof conditions, adding ethanol precipitation after the reaction, filtering, washing, and freeze-drying to obtain sodium aldehyde carboxymethyl cellulose;

[0015] S5. Add the composite modified starch, modified aminopropyl POSS in step S3 and the sodium aldehyde carboxymethyl cellulose in step S4 into deionized water for mixing and dispersion, raise the temperature to 35-45° C., adjust the system pH to 4-5, stir at a constant temperature for 12-16 hours, and after the reaction is completed, freeze-dry to obtain a binder.

[0016] In a self-heating body, components such as active metals and carbon powder are often added. In order to enable the components to be closely combined to exert the primary battery reaction and improve the heating performance, it is very necessary to add a binder. Although conventional binders have certain bonding properties, they are not suitable for powders, especially active metals and carbon powders with huge mass differences. Due to the huge mass difference between active metals and carbon powders, when mixed, the active metals will gather in the bottom layer due to the different weights, while the carbon powders will gather in the upper layer. The two cannot fit closely together, which seriously affects the performance of the self-heating body.

[0017] The adhesive of the present application can solve the above problems and has good bonding performance, anti-thermal expansion performance and anti-aging performance. The reason may be that the adhesive of the present application uses starch and sodium carboxymethyl cellulose as main raw materials, and the starch and carboxymethyl cellulose are modified and then combined by Schiff base to form a cross-linked structure. On the one hand, the side chain structure of the adhesive has phenyl, pyridine, hydroxyl and carboxyl groups, among which pyridine, hydroxyl and carboxyl groups can form coordination bonds with active metals to anchor the metals on the adhesive, and phenyl can form a π-π stacking effect with carbon powder. Anchored on the binder, the active metal and the carbon powder are tightly fitted together, avoiding the problem of uneven dispersion of the active metal and the carbon powder due to quality difference; secondly, the binder of the present application has a cross-linked structure, which improves the viscosity of the binder, and the structure is stable and can resist thermal expansion; thirdly, the binder structure contains a large amount of hindered phenol structure, which can improve the anti-aging performance of the binder; fourthly, the main raw materials of the binder of the present application are starch and sodium carboxymethyl cellulose, so that the prepared binder has good biodegradability, is environmentally friendly, and has no secondary pollution.

[0018] In some embodiments, the structure of the modified aminopropyl POSS is as shown in Formula I

[0019]

[0020] In some embodiments, the preparation method of the modified aminopropyl POSS comprises the following steps:

[0021] A1. Mix sodium hydroxide solution and acetone, cool to -20 to -10°C, add 3-aminopropyltrimethoxy, stir at constant temperature for 20 to 30 minutes, then raise the temperature to reflux, stir for 22 to 26 hours, adjust the pH of the system to neutral after the reaction, filter, concentrate and dry under reduced pressure to obtain aminopropyl POSS;

[0022] A2, the aminopropyl POSS in step A1 is mixed with 2,6-di-tert-butyl-4-chlorophenol and 1-chloronaphthalene, and added into N,N-dimethylformamide, an acid binding agent is added, the temperature is raised to 35-45° C. and stirred at a constant temperature for 12-14 h, and after the reaction is completed, the modified aminopropyl POSS is filtered to obtain.

[0023] The modified aminopropyl POSS of the present application can cooperate with the composite modified starch and sodium aldehyde carboxymethyl cellulose to simultaneously undergo a Schiff base reaction to form a cross-linked structured binder. The phenyl group in the modified aminopropyl POSS can undergo a π-π stacking effect with the carbon powder to anchor the carbon powder. In addition, the hindered phenol structure therein can enhance the anti-aging properties of the binder.

[0024] In some embodiments, in step S1, the mass of the 2,3-pyridinedicarboxylic acid anhydride is 30-40 wt % of the starch.

[0025] The present application can prevent the viscosity of the binder from being too high by regulating the mass ratio of 2,3-pyridinedicarboxylic acid anhydride and starch, which not only makes processing difficult but also is not conducive to the dispersion of active iron powder and carbon powder.

[0026] In some embodiments, the acid binding agent is any one of sodium carbonate, potassium carbonate, sodium bicarbonate and potassium bicarbonate.

[0027] In some embodiments, in step S2, the mass ratio of thionyl chloride to pyridine-modified starch is 1:(0.1-0.3).

[0028] In some embodiments, in step S3, the volume mass ratio of the N,N-dimethylformamide to the acyl chloride modified starch is 8 to 15 mL / g.

[0029] In some embodiments, in step S3, the molar ratio of the acid binding agent to 1,4-butanediamine is (1.2-1.5):1.

[0030] In some embodiments, the molar ratio of the 1,4-butanediamine to the 2,3-pyridinedicarboxylic anhydride is (0.8-1):1.

[0031] The present application can prevent the composite modified starch from self-crosslinking by regulating the molar ratio of 1,4-butanediamine to 2,3-pyridinedicarboxylic anhydride, thereby preventing the composite modified starch from being unable to form a crosslinked structure with the carboxymethyl fiber, thereby causing the dispersion ability of the active metal and the carbon powder to deteriorate.

[0032] In some embodiments, in step S5, the mass ratio of the composite modified starch, modified aminopropyl POSS and sodium aldehyde carboxymethyl cellulose is (0.1-0.3):(0.05-0.15):1.

[0033] The present application can prevent the system from being too viscous due to excessive crosslinking density and being unfavorable for the dispersion effect by regulating the mass ratio of the composite modified starch, modified aminopropyl POSS and aldehyde carboxymethyl cellulose sodium; in addition, it can also prevent the decrease of the anti-thermal expansion performance.

[0034] In some embodiments, the starch is selected from amylose, and the number average molecular weight is 4×10 5 ~9×10 5 g / mol.

[0035] The present application selects amylose with a specific number average molecular weight, which is more easily cross-linked with sodium carboxymethyl cellulose, thereby improving the dispersion performance of active metals and carbon powders. In addition, it can prevent the viscosity of the binder from being too high, which is not conducive to dispersion.

[0036] In some embodiments, in step A2, the molar ratio of aminopropyl POSS, 2,6-di-tert-butyl-4-chlorophenol and 1-chloronaphthalene is 1:(0.8-1):(6-6.2).

[0037] Another aspect of the present invention provides an adhesive prepared according to the above scheme.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] (1) The binder of the present invention uses environmentally friendly and biodegradable natural extract starch and sodium carboxymethyl cellulose as starting materials. The starch and sodium carboxymethyl cellulose are modified separately so that the two can form a Schiff base and then form a cross-linked structure. The binder can make the active metal and the carbon powder fit together tightly, avoiding the problem of uneven dispersion of the active metal and the carbon powder due to quality differences. In addition, the binder also has good anti-aging performance and anti-thermal expansion performance.

[0040] (2) The composite modified starch of the present invention contains pyridine and hydroxyl groups on its side chains, which can form coordination bonds with active metals to anchor the active metals, while the amine groups therein can form Schiff bases with the aldehyde groups in aldehyde carboxymethyl cellulose sodium to form cross-linked binders.

[0041] (3) The modified aminopropyl POSS of the present invention can cooperate with the composite modified starch and sodium aldehyde carboxymethyl cellulose to simultaneously undergo a Schiff base reaction to form a cross-linked structure binder. The phenyl group in the modified aminopropyl POSS can undergo a π-π stacking effect with the carbon powder to anchor the carbon powder. In addition, the hindered phenol structure therein can enhance the anti-aging performance of the binder. DETAILED DESCRIPTION

[0042] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0043] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0044] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as commonly understood by those skilled in the art. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention. Various modifications and variations may be made to the specific embodiments of the present invention specification without departing from the scope or spirit of the present invention, which will be apparent to those skilled in the art. Other embodiments obtained from the present invention specification will be apparent to the technician. The present application specification and examples are exemplary only.

[0045] It should be noted that the operations of "drying", "filtering" and "stirring" described in the present invention are routine operations of those skilled in the art and can be selected according to actual operations.

[0046] In the following preparation examples, the number average molecular weight of amylose is 6×10 5 g / mol; CAS number of sodium carboxymethyl cellulose is 9004-32-4.

[0047] Preparation Example 1

[0048] The preparation method of modified aminopropyl POSS comprises the following steps:

[0049] A1, 10mL 2wt% sodium hydroxide solution was mixed with 100mL acetone, cooled to -15°C, 0.1mol 3-aminopropyl trimethoxy was added thereto, and the mixture was stirred at a constant temperature for 25min, then the temperature was raised to reflux, and stirred for 24h. After the reaction was completed, 1mol / L dilute hydrochloric acid was added to adjust the pH of the system to 6.5, and the mixture was filtered, concentrated under reduced pressure and dried to obtain aminopropyl POSS;

[0050] A2. Mix 0.1 mol of the aminopropyl POSS in step A1 with 0.009 mol of 2,6-di-tert-butyl-4-chlorophenol and 0.61 mol of 1-chloronaphthalene, add into 1 L of N,N-dimethylformamide, add 1 mol of sodium bicarbonate, raise the temperature to 40° C. and stir for 13 h. After the reaction is completed, filter to obtain modified aminopropyl POSS.

[0051] Preparation Example 2

[0052] The preparation method of modified aminopropyl POSS is the same as that of Preparation Example 1, except that 2,6-di-tert-butyl-4-chlorophenol is not added.

[0053] Preparation Example 3

[0054] The preparation method of modified aminopropyl POSS is the same as that of Example 1, except that the amount of 1-chloronaphthalene is 0.4 mol.

[0055] Example 1

[0056] A method for preparing a binder for improving the uniformity of dispersion of a self-heating body comprises the following steps:

[0057] S1. 10 g of amylose was dispersed in 50 mL of deionized water, the temperature was raised to 35° C., the pH of the system was adjusted to 8.5 with a 1 wt % sodium hydroxide solution, and then 20 mL of an aqueous solution containing 3.5 g of 2,3-pyridinedicarboxylic acid anhydride was added thereto, and the mixture was stirred at a constant temperature for 3 h. During this period, the pH of the system was controlled to be unchanged. After the reaction was completed, the pH was adjusted to 7 with 1 mol / L dilute hydrochloric acid, and the mixture was rinsed with anhydrous ethanol and dried to obtain pyridine-modified starch;

[0058] S2, cooling 60g of thionyl chloride to -3°C, then adding the pyridine-modified starch obtained in step S1, stirring at a constant temperature for 2h, filtering after the reaction, washing with ethanol, and drying to obtain acyl chloride-modified starch;

[0059] S3, mixing the acyl chloride modified starch obtained in step S2 with 132 mL of N,N-dimethylformamide, adding 1.86 g of 1,4-butanediamine and 2.56 g of sodium bicarbonate, heating to 55° C. and stirring at a constant temperature for 16 h, washing with deionized water after the reaction, concentrating and drying under reduced pressure to obtain a composite modified starch;

[0060] S4, 70g sodium carboxymethyl cellulose was mixed with 1L deionized water, the temperature was raised to 35°C and the mixture was stirred at a constant temperature for 14h, 700mL of 0.11g / mL NaIO4 solution was added thereto, the pH was adjusted to 2.5 with 1mol / L H2SO4, the mixture was stirred at a constant temperature for 5h under light-proof conditions, and after the reaction was completed, ethanol was added for precipitation, the mixture was filtered, washed, and freeze-dried to obtain aldehyde sodium carboxymethyl cellulose;

[0061] S5. Add 13 g of the composite modified starch in step S3, 6.5 g of modified aminopropyl POSS and 65 g of sodium aldehyde carboxymethyl cellulose in step S4 into 1.5 L of deionized water for mixing and dispersion, raise the temperature to 40°C, adjust the system pH to 4.5, stir at a constant temperature for 14 h, and after the reaction is completed, freeze-dry to obtain a binder.

[0062] Wherein, the modified aminopropyl POSS is prepared by Preparation Example 1.

[0063] Example 2

[0064] A method for preparing a binder for improving the uniformity of dispersion of a self-heating body comprises the following steps:

[0065] S1. 10 g of amylose was dispersed in 50 mL of deionized water, the temperature was raised to 30° C., the pH of the system was adjusted to 8 with a 2 wt % sodium hydroxide solution, and then 20 mL of an aqueous solution containing 3 g of 2,3-pyridinedicarboxylic anhydride was added thereto, and the mixture was stirred at a constant temperature for 2 h. During this period, the pH of the system was controlled to be unchanged. After the reaction was completed, the pH was adjusted to 6.5 with 1 mol / L dilute hydrochloric acid, and the mixture was rinsed with anhydrous ethanol and dried to obtain pyridine-modified starch;

[0066] S2, cooling 40g of thionyl chloride to -5°C, then adding the pyridine-modified starch obtained in step S1, stirring at a constant temperature for 3h, filtering after the reaction, washing with ethanol, and drying to obtain acyl chloride-modified starch;

[0067] S3, mixing the acyl chloride modified starch obtained in step S2 with 96 mL of N,N-dimethylformamide, adding 1.41 g of 1,4-butanediamine and 1.6 g of sodium bicarbonate, heating to 50° C. and stirring at a constant temperature for 18 h, washing with deionized water after the reaction, concentrating and drying under reduced pressure to obtain a composite modified starch;

[0068] S4, 140g sodium carboxymethyl cellulose was mixed with 2L deionized water, the temperature was raised to 30°C and the mixture was stirred at a constant temperature for 16h, 1400mL 0.11g / mL NaIO4 solution was added thereto, the pH was adjusted to 2 with 1mol / L H2SO4, the mixture was stirred at a constant temperature for 6h under light-proof conditions, and after the reaction was completed, ethanol was added for precipitation, the mixture was filtered, washed, and freeze-dried to obtain aldehyde sodium carboxymethyl cellulose;

[0069] S5. Add 13 g of the composite modified starch in step S3, 6.5 g of modified aminopropyl POSS and 130 g of the sodium formaldehyde carboxymethyl cellulose in step S4 into 2 L of deionized water for mixing and dispersion, raise the temperature to 35° C., adjust the system pH to 4, stir at a constant temperature for 16 h, and after the reaction is completed, freeze-dry to obtain a binder.

[0070] Wherein, the modified aminopropyl POSS is prepared by Preparation Example 1.

[0071] Example 3

[0072] A method for preparing a binder for improving the uniformity of dispersion of a self-heating body comprises the following steps:

[0073] S1. 10 g of amylose was dispersed in 50 mL of deionized water, the temperature was raised to 40° C., the pH of the system was adjusted to 9 with a 2 wt % sodium hydroxide solution, and then 20 mL of an aqueous solution containing 4 g of 2,3-pyridinedicarboxylic anhydride was added thereto, and the mixture was stirred at a constant temperature for 4 h. During this period, the pH of the system was controlled to remain unchanged. After the reaction was completed, the pH was adjusted to 7.5 with 1 mol / L dilute hydrochloric acid, and the mixture was rinsed with anhydrous ethanol and dried to obtain pyridine-modified starch;

[0074] S2, cooling 120g of thionyl chloride to 0°C, then adding the pyridine-modified starch obtained in step S1, stirring at a constant temperature for 1h, filtering after the reaction, washing with ethanol, and drying to obtain acyl chloride-modified starch;

[0075] S3, mixing the acyl chloride modified starch obtained in step S2 with 96 mL of N,N-dimethylformamide, adding 2.36 g of 1,4-butanediamine and 3.37 g of sodium bicarbonate, heating to 60° C. and stirring at a constant temperature for 12 h, washing with deionized water after the reaction, concentrating and drying under reduced pressure to obtain a composite modified starch;

[0076] S4, 70g sodium carboxymethyl cellulose was mixed with 1L deionized water, the temperature was raised to 35°C and the mixture was stirred at a constant temperature for 14h, 700mL of 0.11g / mL NaIO4 solution was added thereto, the pH was adjusted to 2.5 with 1mol / L H2SO4, the mixture was stirred at a constant temperature for 5h under light-proof conditions, and after the reaction was completed, ethanol was added for precipitation, the mixture was filtered, washed, and freeze-dried to obtain aldehyde sodium carboxymethyl cellulose;

[0077] S5. Add 13 g of the composite modified starch in step S3, 6.45 g of modified aminopropyl POSS and 43 g of sodium aldehyde carboxymethyl cellulose in step S4 into 1 L of deionized water for mixing and dispersion, heat to 45°C, adjust the system pH to 5, stir at a constant temperature for 12 h, and after the reaction is completed, freeze-dry to obtain a binder.

[0078] Wherein, the modified aminopropyl POSS is prepared by Preparation Example 1.

[0079] Example 4

[0080] A method for preparing a binder for improving the uniformity of dispersion of a self-heating body. The specific implementation method is the same as that of Example 1, except that the modified aminopropyl POSS is prepared by Preparation Example 2.

[0081] Example 5

[0082] A method for preparing a binder for improving the uniformity of dispersion of a self-heating body. The specific implementation method is the same as that of Example 1, except that the modified aminopropyl POSS is prepared by Preparation Example 3.

[0083] Example 6

[0084] A method for preparing a binder for improving the uniformity of dispersion of a self-heating body, wherein the specific implementation manner is the same as that of Example 1, except that the amount of 2,3-pyridinedicarboxylic anhydride is 4 g.

[0085] Example 7

[0086] A method for preparing a binder for improving the uniformity of dispersion of a self-heating body, wherein the specific implementation manner is the same as that of Example 1, except that the amount of 2,3-pyridinedicarboxylic anhydride is 2 g.

[0087] Comparative Example 1

[0088] A method for preparing a binder for improving the uniformity of dispersion of a self-heating body, wherein the specific implementation manner is the same as that of Example 1, except that an equal molar amount of 3-(3-pyridyl) propionic acid is used instead of 2,3-pyridinedicarboxylic anhydride.

[0089] Comparative Example 2

[0090] A method for preparing a binder for improving the uniformity of dispersion of a self-heating body, wherein the specific implementation manner is the same as that of Example 1, except that modified aminopropyl POSS is not added in step S5.

[0091] Comparative Example 3

[0092] A method for preparing a binder for improving the uniformity of dispersion of a self-heating body, the specific implementation method is the same as that of Example 1, except that an equal mass of amylopectin is used instead of amylose, and the number average molecular weight of amylopectin is 826×10 6 g / mol.

[0093] Comparative Example 4

[0094] A method for preparing a binder for improving the uniformity of dispersion of a self-heating body, the specific implementation method is the same as that of Example 1, except that in step S5, an equal mass of amylose is used instead of the composite modified starch.

[0095] Comparative Example 5

[0096] A method for preparing a binder for improving the uniformity of dispersion of a self-heating body comprises the following steps:

[0097] S1, cooling 60g of thionyl chloride to -3°C, then adding 12g of amylose thereto, stirring at a constant temperature for 2h, filtering after the reaction, washing with ethanol, and drying to obtain acyl chloride modified starch;

[0098] S2, mixing the acyl chloride modified starch obtained in step S1 with 132 mL of N,N-dimethylformamide, adding 2.06 g of 1,4-butanediamine and 2.56 g of sodium bicarbonate, heating to 55° C. and stirring at a constant temperature for 16 h, washing with deionized water after the reaction, concentrating and drying under reduced pressure to obtain a composite modified starch;

[0099] S3, 70g sodium carboxymethyl cellulose was mixed with 1L deionized water, the temperature was raised to 35°C and the mixture was stirred at a constant temperature for 14h, 700mL 0.11g / mL NaIO4 solution was added thereto, the pH was adjusted to 2.5 with 1mol / L H2SO4, the mixture was stirred at a constant temperature for 5h under light-proof conditions, ethanol was added to precipitate after the reaction was completed, the mixture was filtered, washed, and freeze-dried to obtain aldehyde sodium carboxymethyl cellulose;

[0100] S4. Add 13 g of the composite modified starch in step S2, 6.5 g of modified aminopropyl POSS and 65 g of sodium aldehyde carboxymethyl cellulose in step S3 into 1.5 L of deionized water for mixing and dispersion, heat to 40°C, adjust the system pH to 4.5, stir at a constant temperature for 14 h, and after the reaction is completed, freeze-dry to obtain a binder.

[0101] Performance Testing:

[0102] (1) Thermal expansion resistance, test according to the following steps:

[0103] Step 1: weigh 58 parts of kaolin, 19 parts of calcined talc, 3 parts of binder, 3 parts of toughening agent, and 1.5 parts of rutile by weight, pour them into a ball mill, add 45 parts of clean water, and grind them evenly to obtain a raw material mixed slurry;

[0104] Step 2, after the raw material mixed slurry is stirred evenly, it is poured into a filter press for filtering and dehydration to obtain a mixed mud cake;

[0105] Step 3, placing the mixed mud cake into a vacuum mud kneading machine for vacuum kneading to obtain a mixed mud material;

[0106] Step 4, placing the mixed clay material into a mold of a spinning machine for spinning molding to obtain a concave plate blank;

[0107] Step 5, sending the above-mentioned concave plate blank into a roller kiln for high-temperature calcination to obtain a finished concave plate after firing; and testing the obtained concave plate using the ASTM C372-17 ceramic product thermal expansion coefficient test method;

[0108] (2) Bond strength test: According to GB / T14074-2017 "Test methods for adhesives and resins for wood industry", the adhesive was evenly coated on two wooden blocks with a size of 40 mm × 20 mm × 15 mm. After bonding, the two blocks were placed in an oven at 100 °C for 1 h and then placed at room temperature for 24 h. A tensile test was performed at a tensile rate of 50 mm / min to test the bond strength.

[0109] (3) Dispersion performance: By weight, 50 parts of iron powder, 4 parts of wood fiber, and 5 parts of activated carbon were mixed evenly, and 1.5 parts of the above-mentioned binder were added and mixed evenly to obtain a uniformly mixed powder. The powder was loaded into a tablet pressing mold with inner packaging materials padded on the top and bottom, and pressed into a square shape to obtain a self-heating body. The center of the self-heating body was placed directly above the temperature probe of a paperless temperature recorder, and a double layer of towels were covered on the top of the heating sheet for insulation. The room temperature, i.e., the starting temperature, was about 25°C. The maximum heating temperature and heating duration were tested. If the iron powder and activated carbon had poor dispersion, the heating temperature and heating duration would be poor.

[0110] (4) Anti-aging performance test: The wood blocks bonded in method (2) were placed in a 100 μ / cm 2 After 1000 hours under UV light and 70°C, the bonding strength was tested.

[0111] The adhesives of the embodiments and comparative examples were tested according to the above method. The test results are shown in Table 1.

[0112] Table 1

[0113]

[0114] According to the data in Table 1, the binders prepared in Examples 1 to 3 have good resistance to thermal expansion, bonding and aging resistance, and can also make the metal powder and carbon powder dispersed evenly to improve the heating performance of the self-heating body; in Example 4, due to the lack of 2,6-di-tert-butyl-4-chlorophenol, the anti-aging performance of the binder is weakened, and the bonding strength after aging is reduced; in Example 5, due to the change in the molar ratio of aminopropyl POSS, 2,6-di-tert-butyl-4-chlorophenol and 1-chloronaphthalene, the performance of the binder in dispersing metal powder and carbon powder is deteriorated, and the heating performance of the self-heating body is deteriorated; in Example 6, due to the change in the molar ratio of 1,4-butanediamine to 2,3-pyridinedicarboxylic anhydride, the heating performance of the heating body prepared by the binder is deteriorated; in Example 7, due to the change in the molar ratio of 1,4-butanediamine to 2,3-pyridinedicarboxylic anhydride, the anti- The thermal expansion performance deteriorates; in Comparative Example 1, since an equal molar amount of 3-(3-pyridyl) propionic acid is used instead of 2,3-pyridinedicarboxylic anhydride, the thermal expansion resistance, bonding performance and anti-aging performance of the adhesive are reduced, and the performance of dispersing metal powder and carbon powder is reduced; in Comparative Example 2, since modified aminopropyl POSS is not added, the dispersion performance of the adhesive deteriorates; in Comparative Example 3, since an equal mass of amylopectin is used instead of amylose, the cross-linking structure of the adhesive is reduced, and the thermal expansion resistance and bonding performance are reduced. At the same time, due to the reduction in cross-linking structure, the functional group content is reduced, which makes the dispersion performance deteriorate; in Comparative Example 4, since amylose is directly used instead of composite modified starch, the thermal expansion resistance and bonding performance of the adhesive are reduced, and the dispersion performance is also reduced; in Comparative Example 5, since 2,3-pyridinedicarboxylic anhydride is not added, the dispersion performance of the adhesive is slightly reduced.

[0115] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a binder for improving the uniformity of dispersion of a self-heating body, characterized in that: The steps include: S1. Disperse starch in deionized water, raise the temperature to 30-40° C., adjust the pH of the system to 8-9, then add an aqueous solution of 2,3-pyridinedicarboxylic anhydride, stir at a constant temperature for 2-4 hours, and control the pH of the system to be unchanged. After the reaction is completed, adjust the pH to neutral, rinse with anhydrous ethanol, and dry to obtain pyridine-modified starch; S2, cooling thionyl chloride to -5 to 0°C, then adding the pyridine-modified starch in step S1, stirring at a constant temperature for 1 to 3 hours, filtering after the reaction, washing with ethanol, and drying to obtain acyl chloride-modified starch; S3, mixing the acyl chloride modified starch in step S2 with N,N-dimethylformamide, adding 1,4-butanediamine and an acid binding agent, heating to 50-60° C. and stirring at a constant temperature for 12-18 hours, washing with deionized water after the reaction, concentrating and drying under reduced pressure to obtain a composite modified starch; S4, mixing sodium carboxymethyl cellulose with deionized water, heating to 30-40°C and stirring at constant temperature for 12-16 hours, then adding NaIO4 solution thereto, adjusting the pH to 2-3, stirring at constant temperature for 4-6 hours under light-proof conditions, adding ethanol precipitation after the reaction, filtering, washing, and freeze-drying to obtain sodium aldehyde carboxymethyl cellulose; S5. Add the composite modified starch, modified aminopropyl POSS in step S3 and the sodium aldehyde carboxymethyl cellulose in step S4 into deionized water for mixing and dispersion, raise the temperature to 35-45° C., adjust the system pH to 4-5, stir at a constant temperature for 12-16 hours, and after the reaction is completed, freeze-dry to obtain a binder.

2. The method for preparing a binder for improving the uniformity of dispersion of a self-heating body according to claim 1, characterized in that: The structure of the modified aminopropyl POSS is shown in Formula I 3. The method for preparing a binder for improving the uniformity of dispersion of a self-heating body according to claim 2, characterized in that: The preparation method of the modified aminopropyl POSS comprises the following steps: A1. Mix sodium hydroxide solution and acetone, cool to -20 to -10°C, add 3-aminopropyltrimethoxy, stir at constant temperature for 20 to 30 minutes, then raise the temperature to reflux, stir for 22 to 26 hours, adjust the pH of the system to neutral after the reaction, filter, concentrate and dry under reduced pressure to obtain aminopropyl POSS; A2, the aminopropyl POSS in step A1 is mixed with 2,6-di-tert-butyl-4-chlorophenol and 1-chloronaphthalene, and added into N,N-dimethylformamide, an acid binding agent is added, the temperature is raised to 35-45° C. and stirred at a constant temperature for 12-14 h, and after the reaction is completed, the modified aminopropyl POSS is filtered to obtain.

4. The method for preparing a binder for improving the uniformity of dispersion of a self-heating body according to claim 1, characterized in that: In step S1, the mass of the 2,3-pyridinedicarboxylic acid anhydride is 30-40 wt % of the amylose.

5. The method for preparing a binder for improving the uniformity of dispersion of a self-heating body according to claim 1, characterized in that: The acid binding agent is any one of sodium carbonate, potassium carbonate, sodium bicarbonate and potassium bicarbonate.

6. The method for preparing a binder for improving the uniformity of dispersion of a self-heating body according to claim 1, characterized in that: The molar ratio of the 1,4-butanediamine to the 2,3-pyridinedicarboxylic anhydride is (0.8-1):

1.

7. The method for preparing a binder for improving the uniformity of dispersion of a self-heating body according to claim 1, characterized in that: In step S5, the mass ratio of the composite modified starch, modified aminopropyl POSS and sodium aldehyde carboxymethyl cellulose is (0.1-0.3):(0.05-0.15):

1.

8. The method for preparing a binder for improving the uniformity of dispersion of a self-heating body according to claim 1, characterized in that: The starch is selected from amylose, and the number average molecular weight is 4×10 5 ~9×10 5 g / mol.

9. The method for preparing a binder for improving the uniformity of dispersion of a self-heating body according to claim 3, characterized in that: In step A2, the molar ratio of aminopropyl POSS, 2,6-di-tert-butyl-4-chlorophenol and 1-chloronaphthalene is 1:(0.8-1):(6-6.2).

10. A binder obtained by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • An environmentally friendly starch adhesive

    CN104629647B

  • An environmentally friendly water-based adhesive

    CN110760282B

  • Binder and battery including the same

    CN114656904B

  • Starch reinforcing agent for production of corrugated board

    CN105113329A

  • High-stability grease composition and preparation method thereof

    CN113549496A

Cited By

  • Self-heating diaphragm core and preparation method thereof

    CN119868045A